2023
DOI: 10.3390/healthcare11162338
|View full text |Cite
|
Sign up to set email alerts
|

Deep Carious Lesions Management with Stepwise, Selective, or Non-Selective Removal in Permanent Dentition: A Systematic Review of Randomized Clinical Trials

Nicola Figundio,
Pedro Lopes,
Tamara Kerber Tedesco
et al.

Abstract: Objective: The goal of this systematic study was to investigate the effectiveness of selective, stepwise, and non-selective removal techniques for caries removal in permanent teeth with deep carious lesions. The primary focus was the results found comparing techniques for caries removal to check whether there was pulp exposition; the secondary was the materials used for pulp protection and clinical findings reported within the included studies. Methods: The search was performed in two databases (PubMed/MEDLINE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…During the setting process, resin composite materials may undergo shrinkage, which causes difficulties in effectively sealing against the tooth surface, potentially leading to the infiltration of bacteria [28]. This phenomenon, known as microleakage, is frequently manifested as marginal staining, postoperative sensitivity, and the development of secondary caries around the restoration site [29].…”
Section: Introductionmentioning
confidence: 99%
“…During the setting process, resin composite materials may undergo shrinkage, which causes difficulties in effectively sealing against the tooth surface, potentially leading to the infiltration of bacteria [28]. This phenomenon, known as microleakage, is frequently manifested as marginal staining, postoperative sensitivity, and the development of secondary caries around the restoration site [29].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews of the literature have concluded that CRCT can be considered an invasive technique with a higher risk of pulpal exposure, making SRCT the best option for treating deep carious lesions in 18-month follow-ups [ 8 , 9 ]. However, there is still significant disagreement among dentists regarding the use of SRCT in deep carious lesions extending to the inner third of dentin without obvious potential pulpal exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The initial stages of dental caries typically manifest as white spot lesions, which can progress to discoloration without timely intervention [ 2 ]. Therapeutic restorative treatment is aimed at eliminating the carious lesion and reinstating the tooth’s original contours and contacts [ 3 ]. With the introduction of adhesive restorative materials, clinicians have the opportunity to choose conservative preparations that facilitate the preservation of maximum tooth structure, while also ensuring aesthetic concern, given that the majority of adhesive restorations are designed to match the natural tooth color [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic restorative treatment is aimed at eliminating the carious lesion and reinstating the tooth’s original contours and contacts [ 3 ]. With the introduction of adhesive restorative materials, clinicians have the opportunity to choose conservative preparations that facilitate the preservation of maximum tooth structure, while also ensuring aesthetic concern, given that the majority of adhesive restorations are designed to match the natural tooth color [ 3 , 4 ]. Dental cements represent restorative materials composed of small biomolecules that demonstrate biocompatibility and contribute positively to tooth structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation